The Students’ Perception Towards the Implementation of Online Classroom Interaction in ESP Class - Farah Anita Firdaus; Nina Inayati; Khoiriyah Khoiriyah (FKIP Universitas Lampung, 2024)
The Students’ Perception Towards the Implementation of Online Classroom Interaction in ESP Class. There are several aspects contributing to the effectiveness of online learning. One of which is interaction. Interaction commonly is divided into three types, such as teacher-students, students-students and students-content interaction. This study aims to analyse the students’ perception about online interaction as well as the challenges of online interaction faced by the students in ESP class. A descriptive quantitative method was used. 125 respondents were selected from students of Management Department in semester two. To collect the data, the researcher adapted online survey questionnaire using Google Form and online semi-structured interview using a video conference. The researcher calculated 20 items of questions based on each respondent and question item answered. Based on the results of this study, it is revealed that the average score of all question items calculated based on each respondent and each question item answered is 76,10%. It was found that students were satisfied with the online interaction such as they were appreciated the instructions given by the teacher, they were excited to have an experience with other students in online discussion, and they preferred the idea of using audio for listening during online interaction. However, students reported that the only major problem found was the lack of internet connection. Meanwhile, other problems also encountered such as less interaction and no direct communication with the teacher which hinder their experience to have effective online interaction. Keywords: ESP, student’s perception, online interactionDOI: http://dx.doi.org/10.23960/jpp.v14.i2.202461